IMPLEMENTASI MEDIA PEMBELAJARAN MADING BERBASIS SASTRA UNTUK MENINGKATKAN KREATIVITAS DAN HASIL BELAJAR SISWA KELAS V SDN NATAKUPE - Veronika Yuliana Beku; Yohanes Vianey Sayangan; Dek Ngurah Laba Laksana; Yosefina Uge Lawe (Universitas Muhammadiyah Makassar, 2025)
This study aims to implement literary -based mading learning media as an innovation in increasing the creativity and learning outcomes of students in class V SDN Natakupe. With a classroom action research approach (CAR) conducted in two cycles, this research integrates literary elements into learning media to create interactive, imaginative and relevant learning experiences. Data collection methods through observation techniques, tests, and interviews using instruments in the form of observation sheets, test questions, and interview guidelines. The results of the first cycle show that the average student creativity reaches 30%and learning outcomes of 55.5%, with a classical completeness of 30%. After the improvement in the second cycle, creativity increased to 90%, learning outcomes reached an average of 80.3%, and classical completeness increased to 80%. Overall, there was an increase in creativity by 60%, learning outcomes of 25.45%and classical completeness of 50%. Observation data and research tests show that this implementation offers a new perspective on the importance of creative and relevant learning media to support literary learning in elementary schools. Based on the results of the study it can be concluded that the implementation of literary -based mading learning media can increase the creativity and learning outcomes of students in class V SDN Natakupe.